Educational planning strategic, tactical, and operational - Kaufman, Roger A.; Watters, Kathi; Herman, Jerry (Lanham, MD Scarecrow Press, 2002)
"Expert presentation of holistic planning for a learner-focused educational system. Integrates curriculum, facilities, personnel, finance, educational technology, and other significant planning tactics."
Preface -- Prologue -- Part One: Strategic planning. -- 1. Why plan strategically? -- 2. Mega-planning: a new and practical paradigm -- 3. Strategic planning starts with the ideal vision -- 4. Identifying mission based on the ideal vision -- 5. Needs assessment -- 6. Transitioning: the planning phase -- Part Two: Tactical planning. -- 7. Tactical planning -- Part Three: Implementation. 8. Integrating strategic planning, quality management, and needs assessment -- 9. Delivering on the strategic plan -- Appendix A: A school district develops a strategic plan: a hypothetical and partial example -- App. B: Dealing with beliefs and values -- App. C: A minimal ideal vision -- Glossary -- References and related readings -- Index -- About the author.
Includes bibliographical references (p. 271-279) and index.
Keywords: Educational planning; Strategic planning